International cohort study indicates no association between alpha-1 blockers and susceptibility to COVID-19 in benign prostatic hyperplasia patients - Nishimura, Akihiko; Xie, Junqing; Kostka, Kristin; Duarte-Salles, Talita; Fernández Bertolín, Sergio; Aragón, María; Blacketer, Clair; Shoaibi, Azza; DuVall, Scott L.; Lynch, Kristine; Matheny, Michael E.; Falconer, Thomas; et al. (Frontiers in Pharmacology, 2022)
Alpha-1 blockers, often used to treat benign prostatic hyperplasia (BPH), have been hypothesized to prevent COVID-19 complications by minimising cytokine storm release. The proposed treatment based on this hypothesis currently lacks support from reliable real-world evidence, however. We leverage an international network of large-scale healthcare databases to generate comprehensive evidence in a transparent and reproducible manner. In this international cohort study, we deployed electronic health records from Spain (SIDIAP) and the United States (Department of Veterans Affairs, Columbia University Irving Medical Center, IQVIA OpenClaims, Optum DOD, Optum EHR). We assessed association between alpha-1 blocker use and risks of three COVID-19 outcomes — diagnosis, hospitalization, and hospitalization requiring intensive services — using a prevalent-user active-comparator design. We estimated hazard ratios using state-of-the-art techniques to minimize potential confounding, including large-scale propensity score matching/stratification and negative control calibration. We pooled database-specific estimates through random effects meta-analysis. Our study overall included 2.6 and 0.46 million users of alpha-1 blockers and of alternative BPH medications. We observed no significant difference in their risks for any of the COVID-19 outcomes, with our meta-analytic HR estimates being 1.02 (95% CI: 0.92 - 1.13) for diagnosis, 1.00 (95% CI: 0.89 - 1.13) for hospitalization, and 1.15 (95% CI: 0.71 - 1.88) for hospitalization requiring intensive services. In summary, we found no evidence of the hypothesized reduction in risks of the COVID-19 outcomes from the prevalent-use of alpha-1 blockers — further research is needed to identify effective therapies for this novel disease.